Preparation of barley and yeast β-glucan scaffolds by hydrogel foaming: evaluation of dexamethasone release - Salgado, M. (2017)
Porous polymeric materials are studied in tissue engineering, because they can act as support for cell proliferation and as drug delivery vehicles for regeneration of tissues. Hydrogel foaming with supercritical CO2 is a suitable alternative for the creation of these structures, since it avoids the use of organic solvents and high temperature in the processing. In this work, Î²-glucans were used as raw materials to create hydrogels due to their easily gelation and biological properties. The enhancement of porosity was generated by a fast decompression after keeping the hydrogels in contact with CO2. The effect of the processing conditions and type of Î²-glucan in the final properties was assessed regarding morphological and mechanical properties. Finally, the ability of these materials to sustainably deliver dexamethasone was evaluated. The scaffolds had good morphology and provided a controlled release, thus being suitable to be used as scaffolds and drug delivery vehicles.